Some Issues in Misrepresentation - KOH, Pearlie (Institutional Knowledge at Singapore Management University, 2008)
While it is not disputed that misrepresentations of all categories are premised on false statements that result in damage (i.e. inducement), there is not clear agreement as to whether the representation needs to be, in addition, material, and what intentions is it necessary to prove, if al all, that the representor had. Often, these elements overlap, and proof of one arguably rises to inferences as to another.